Organizational Culture Transformation and Its Impact on Performance in the Digital Era - Adam, Adam; Siladjaja, Muljanto (Dinasti International Journal of Management Science, 2025)
Organizational culture transformation has become an urgent need in the digital era, marked by rapid technological advancements and changing work patterns. This article discusses how organizational culture transformation impacts employee performance and the overall organization. The research is conducted through literature review and empirical analysis, revealing that adopting digital cultural values, such as collaboration, innovation, and flexibility, plays a crucial role in enhancing productivity and organizational competitiveness. Additionally, this transformation requires leadership commitment to create an adaptive work environment, empower employees through digital training, and ensure transparent communication. These findings provide insights for leaders to prioritize culture transformation as a key strategy to address digital era challenges and achieve organizational sustainability. Organizational culture transformation also faces challenges such as resistance to change, digital skills gaps, and the need for work process restructuring. Therefore, successful organizational culture transformation necessitates a holistic approach that includes strategic planning, stakeholder engagement, and continuous evaluation to ensure the changes align with the organization’s vision and mission. The implications of this cultural transformation extend beyond improving organizational performance. It also contributes to individual employee development, fosters a more inclusive work environment, and encourages diversity in ideas and innovation. Thus, organizational culture transformation becomes a critical element in creating sustainable competitiveness amidst increasingly intense global competition.